PENGARUH PENERAPAN MODEL PICTURE AND PICTURE PROGRAM MIND ON YOUR OWN BUSINESS, METODE CERAMAH TERHADAP HASIL BELAJAR AKUNTANSI - Korosando Fransiskus; Manggu Ngguna Raji; Elvira Fransiska (Jurnal Visi Ilmu Pendidikan, 2022)
ABSTRACTThis study aims to describe the application of the image model and MYOB accounting program and the lecture method, the differences in the learning outcomes of students in class XI SMK Yos Sudarso Ende. This experimental research uses the method of observation and tests. Explained with the next quantitative approach. Improved learning outcomes were tested with N-Gain and analyzed by t-test.Initial test results; the average value of the experimental group was 8.50, the control group was 8.67. The standard deviation of the experimental group (S1) was 2.505, the control group was 1.670. Post-test results; the average value of the experimental group was 19.42, the control group was 14.92. The Standard deviation (S2) of the experimental group was 2,938, the control group was 3,343. The N-Gain group of the experimental group had 58.33% "moderate" classification, 41.7% "high" classification. The control group N-Gain had 33.33% "low" classification, 58.33% "moderate" classification, and 8.33% high classification. The t-test shows t count t table or 3.503> 1.717 so that H0 is rejected. In conclusion, there are differences in learning outcomes between the experimental group and the control group.